Dampak Negatif Sosial Media Terhadap Anak Dibawah Umur - Renindita Renindita; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The power of social media lies in its ability to harness the collective intelligence of its users by actively involving them and soliciting their input from diverse groups. The use of social media for public relations purposes can have unintended consequences if not handled with care. Analysing, describing, and illustrating the negative effects of social media on minors as well as efforts to counteract these effects are the primary goals of this research. This study takes a conceptual approach to research, making it normative. First, the negative effects of social media on children include stunted development, health problems, increased risk of criminal behaviour and cyberbullying, impaired language skills, and unhealthy comparisons with others. Second, teacher educators can do their part to mitigate the negative effects of social media on youth by banning smartphone use in the classroom, parents can set limits on when and how much time their children can spend on social media, policymakers can take action through legislation and outreach, and members of the community can work together to make their neighbourhoods safer and healthier for teens.